Makna dan Hakikat Serta Tujuan Kurikulum - Nadhila Mastura; Amril M; Sukmawati Sukmawati (FKIP, Universitas Palangka Raya, 2025)
This research aims to determine the meaning, nature, and objectives of the curriculum. This type of research is qualitative, using descriptive analysis methods and library study methods to dig up information. Curriculum is a set of things related to learning, starting with planning, implementation, and evaluation, and concerns the programs, facilities, and activities of an educational or training institution to realize its vision, mission, and institution. There are four goals of the curriculum: national education goals, institutional education goals, curricular goals, and learning goals.